2014
DOI: 10.1007/s00380-014-0547-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor suppresses hypoxia/reoxygenation-induced XO activation in cardiac microvascular endothelial cells

Abstract: Hypoxia/reoxygenation (H/R) is one of the cellular stresses in pathological conditions, such as myocardial infarction, stroke and organ transplantation. Oxidative stress caused by reactive oxygen species (ROS) is a crucial element of H/R injury in vascular endothelial cells (ECs). Xanthine oxidase (XO) has been recognized to contribute to H/R injury. Of note, xanthine oxidoreductase is synthesized as xanthine dehydrogenase (XDH) and needs to be converted to XO to become a source of superoxide. Hepatocyte growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…It has also been reported that HGF has an anti‐inflammatory effect on the chronic kidney disease rat model . Interestingly, recent studies have shown that HGF protected cardiac microvascular endothelial cells against oxidative damage induced by hypoxia/reoxygenation . Based on these studies, we aimed to study the protective effect of HGF in MSCs exposed to harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that HGF has an anti‐inflammatory effect on the chronic kidney disease rat model . Interestingly, recent studies have shown that HGF protected cardiac microvascular endothelial cells against oxidative damage induced by hypoxia/reoxygenation . Based on these studies, we aimed to study the protective effect of HGF in MSCs exposed to harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…7 Interestingly, recent studies have shown that HGF protected cardiac microvascular endothelial cells against oxidative damage induced by hypoxia/reoxygenation. 8 Based on these studies, we aimed to study the protective effect of HGF in MSCs exposed to harsh conditions. For this, we constructed a plasmid overexpressing HGF gene and investigated the effect of HGF-overexpression in MSCs.…”
mentioning
confidence: 99%
“…Despite the well-characterized increase in XO activity generating ROS during I/R injury [29], most studies are still trying to characterize the mechanisms of XO regulation, including the increase in XOR expression [2] and redox modifications due to I/R injury [6, 30]. In this respect, this is a pioneering study evaluating XO activity in post-CA patients who received MTH.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of intracellular Ca 2+ levels causes the conversion of xanthine dehydrogenase to XO [53,56], which produces superoxide. Superoxide, either directly or after conversion to •OH [57], damages the biological membranes [58] and other cellular components, including DNA [59], resulting in cell death.…”
Section: Calcium Overload and •Oh Generationmentioning
confidence: 99%